Glutamine-330 is not essential for activity in isopenicillin N synthase from Aspergillus nidulans. - Sami, M; Brown, T; Roach, P; Schofield, C; Baldwin, J (1997)
The non-heme ferrous dependent oxidase isopenicillin N synthase (IPNS) catalyses the biosynthesis of isopenicillin N from a tripeptide substrate. The crystal structure of Aspergillus nidulans IPNS complexed to manganese reveals a six co-ordinate metal ligated by two water molecules and four protein ligands: His-214, His-270, Asp-216 and Gln-330 (the penultimate C-terminal residue). Modification of Gln-330 to Ala or Leu, or deletion of 2 or 6 residues from the C-terminus resulted in lowering of specific activity; no activity was observed after deletion of 8 residues. The results demonstrate that metal ligation by Gln-330 is not required for catalytic activity.